Corporate Social Responsibility Disclosure and Company Financial Performance: Do High and Low Profile Industry Moderate the Result? - Rafael Martin; Winwin Yadiati; Arie Pratama (Indonesian Journal of Sustainability Accounting and Management, 2018)
The purpose of this research is to find out whether how much the effect of corporate social responsibility disclosure to company financial performance that was measured by sales growth and return on asset. High and low profile were added to test whether it can moderate the results. The method that were used in this research is a verification analysis. The sample company consisted of 21 companies where 12 of those companies were belong to high profile category and 9 of those were belong to low profile category and also listed in Indonesia Stock Exchange (IDX) within period of 2013-2015. The statistical testing that is used in this research was double linear regression with a significance value of 5%. The result from this research found that the corporate social responsibility disclosure doesn’t have positive and significant effect on sales growth. On the other hand, corporate social responsibility disclosure has a positive and significant effect on return on asset. After industry classification as a moderating variable were taken into account, corporate social responsibility disclosure become non-significant to both sales growth and return on asset. It can be said that high and low profile industry in Indonesia didn’t differ significantly in terms of their corporate social responsibility actions.